(untitled) (KYAMC Journal, 2019)
Background: Intravenous dexamethasone may produce perineal pruritus in some patients when administered as premedicant before induction of anesthesia. Objectives of study: This randomized, double-blind study was done to evaluate the efficacy of pretreatment of lignocaine on the incidence and severity of dexamethasone-induced perineal pruritus. Materials and methods: 100 patients were enrolled in this study and allocated randomly into two equal groups. Then, patients received intravenous medications in the following sequence before induction of anesthesia: in group I, injection lignocaine 1mg/kg diluted in 5 ml normal saline and in group II, 5 ml normal saline (placebo group), then one minute later, intravenous dexamethasone sodium phosphate 10 mg was given in all groups in 3 seconds and was observed the patient’s response about perineal pruritus. The severity of perineal pruritus was graded based on the visual analog scale (VAS) as none (VAS 0), mild (VAS 1-3), moderate (VAS 4-6), or severe (VAS 7-10), and recorded the incidence and severity of perineal pruritus. Then general anesthesia was induced and continued as usual. Results: In terms of demographic data, the results of this study showed that there was no significant difference between patients in both groups (P>0.05). Overall incidence and severity of perineal pruritus in lignocaine group was significantly less, when compared with placebo group (P<0.05). Conclusion: It can be concluded that pretreatment with 1mg/kg intravenous lignocaine may effectively reduce the incidence and severity of dexamethasone induced perineal pruritus. KYAMC Journal Vol. 9, No.-4, January 2019, Page 144-147